Efforts to Grow the Character and Behavior of Pro-Environment and Agriculture from an Early Age with Quantum Learning Method at SDN Kalianyar 2 Bondowoso - Masadi, Melody Angel; Maulana, Husaini; Chandra, Alicia Cherie; Latif, Abdul; Munawar, Fahad Fauzan Al; Ikhsan, Nurman Maulana; Fahrudin, Danil Eka; Afifah, Nur; Rahmawati, Irma; Safrillah, M. Rizky Eka Putra Vi (Universitas Nahdlatul Ulama Surabaya, 2023)
The interest of young generation towards the agricultural sector and agriculture regeneration in Indonesia is declining. Therefore, this program exists to increase and develop an awareness of the needs of actors in the agricultural sector by inviting 4th-grade students of SDN Kalianyar 2 to care about the environment, as well as improving their education about agriculture. The methods of learning used were the quantum learning method which are ways for students to learn while having fun. Based on the activities that have been carried out, it can be concluded that the following four things, can raise a sense of concern for the environment and agriculture in students at SDN Kalianyar 2, this activity gets a positive response from all school parties, both from teachers and students.